Strategi Pengelolaan Wisata Syariah Kota Pekanbaru - Mufti Hasan Alfani; Putri Nuraini; Muhammad Arif; Ag Maulana (COSTING : Journal of Economic, Business and Accounting, 2020)
The legacy of the Malay kingdom of Riau has become a valuable historical site as one of the areas of the Islamic kingdom which has become a current sharia tourist destination. The purpose of this study was to determine the management strategy of the Riau Province An-Nur Grand Mosque, the Ar-Rahman Grand Mosque in Pekanbaru City, and the Senapelan Grand Mosque in Pekanbaru City as religious tourism destinations in Pekanbaru City. The techniques used in data collection are observation, interviews, documentation, and analyzing books related to research. The data analysis used was an interactive analysis model. The results of this study illustrate that 1. The implementation of planning in Islamic tourism in Pekanbaru City through the formation of the board 2. The implementation of the organization that has been formed by the management in managing the mosque as a religious tourism destination based on the main task and schedule made as a form of board coordination 3. Implementation of the movement has followed training and comparative studies of mosque administrators as religious tourism and providing salaries or wages to administrators 4. Controlling Implementation of Sharia Tourism management in Pekanbaru City is included in asset instruments under government control and supervision as the Pekanbaru City Grand Mosque 5. Marketing through promotion has been implemented with several types of online and print media. 6. Financial implementation is carried out with a system of transparency and accountability based on predetermined standards. 7. Operational implementation of activities that have been carried out routine mosques such as prayer 5 times, majlis taklim, tabligh akbar and other religious activities 8. The application of R & D from the development of mosques as religious tourism destinations in Pekanbaru City received attention from the local government as a Raya and Paripurna mosque that has budget and expenditure on the running of mosque activities in the religious activity program in Pekanbaru City 9. Implementation of the Information System Mosque has been carried out in the information system on the management of religious tourism at the Great Mosque of An-Nur, Riau Province. Keywords: Strategy, Management, Sharia Tourism